The Portrayal of President A. Duda’s and Prime Minister D. Tusk’s Visit to the United States on the Websites of Selected Radio Stations - Paszko, Sara (The phenomena of propaganda and manipulation in the press, radio, television, and internet. Volume III, 2025)
In contemporary media studies, one can observe the process of mediatization of politics, which involves the mediation of mass media in reporting socially significant events. As a result, the media assign new meanings to the events they describe, which in turn shapes the media image of a given event in the audience’s mind.This article offers a media studies perspective on the portrayal of the visit of President A. Duda and Prime Minister D. Tusk to the United States in March 2024.The research material consisted of the websites of nationwide radio stations recognized by the Institute of Media Monitoring as the most influential in shaping public opinion. The selected websites were Polskie Radio 24, RMF24, TOK FM, and Radio ZET. Both quantitative and qualitative methods were applied, enabling a framing analysis of the studied content.The results of the analysis indicate that the examined websites engaged in a discourse related to the Polish delegation’s visit to the USA; however, it was marginal compared to other content published during the studied period. It was also observed that the analyzed sources partially reproduced certain materials, while the most distinctive ones were those that synthesized or transmitted interviews aired on the selected radio stations. Furthermore, it was demonstrated that the dominant frame was the “responsibility frame,” whose high frequency is associated with the political dimension of the analyzed content.